Analysis of Total Quality Management for Product Quality Control CV. Melai Fresh Baubau City - Sumantri, Sri; Da’a, Fitrianti; La Masu, Nur Erwian (Malikussaleh University, Aceh, Indonesia, 2025)
This research aims to determine and analyze Total Quality Management (TQM) for product quality control at CV. Melai Fresh Baubau City. The data type used is qualitative data, and the data sources used are primary and secondary. The data collection techniques used were direct observation (observation), interviews and documentation, which were then analyzed using qualitative descriptive analysis. This research shows that CV has implemented Total Quality Management (TQM) for product quality control. Melai Fresh. Through Total Quality Management (TQM), CV. Melai Fresh has positively impacted the company's development and progress, even though customer satisfaction is still lacking in service, by implementing Total Quality Management (TQM) CV. Melai Fresh can optimize the performance of all departments to provide the best quality; in this case, quality is the primary concern for the products produced and their management, improving company strategy, team member performance, and decision-making based on facts. To control product quality at CV. Melai Fresh has also been implemented based on product quality dimensions. Product quality control has been implemented to improve product quality per the company's operational standards and produce products that comply with specifications, from raw materials processing to finished product processes. Apart from that, it can also reduce damage/defects to the product.